Urgensi Pembentukan Lembaga Eksekutor dalam Eksekusi Putusan Pengadilan Tata Usaha Negara - Nurfajrin Ramadhan; Nila Sastrawati (Alauddin Law Development Journal (ALDEV), 2022)
The subject of this research reinforces the concept of the governance of the state by wich the verdict should be executed by any state governance body and the limitation of presidential authority as authorized in executing every judicial decision of state governance in accordance with the statement of 116 verse 5 (5) the 1986 article no. 5 The comprehensive author seeks to review and analyze several decisions in the state governance courts that are not yet fully impelemented and analyze the presidential commission mechanism in executing a state ordinance ruling that should be indifferent to the ruling and a juxo philosophical comparison of the 1986 no. 5 act on the judicial system of state, The 2004 act no. 9 on the first change to act no. 5 in 1986 on the second change to act 5 in 1986 on the state administrative judicial being derivated throught several points: 1) How should a judicial decision in a state governance court be carried out?, 2) What are the limits of the authority of the executioners in the execution of the state ordinance judicial decisions?. The type of research used in this study is the normative-based library (library research). Legislation as a primary source and various literature derived from books, journals, papers, scripts, as well as articles secondary to the conceptual approach. The study suggest that: 1) The absence of executioners in executing individual state governance judicial decisions leaves many officials who have not carried out the ruling. 2) The president’s authorization to execute each judicial decision of state enterprises also does not have a positive effect on the administration of state governance. As for the implications the author gets: 1) The need for an executive body to be formed in executing judgement rulings of state enterprises that are obliged to impose and oversee whether the ruling is ignored by state adminisitrators or not. 2) The need for the ruling to be carried out by the official/administration of the state after amar verdict has been read by the judge to make sure that the certainly of the law as the goal of the law is realized.